A Top Coat with Solvent Annealing Enables Perpendicular Orientation of Sub‐10 nm Microdomains in Si‐Containing Block Copolymer Thin Films. (1st September 2014) - Kim, Eunjin; Kim, Wonjung; Lee, Kwang Hee; Ross, Caroline A.; Son, Jeong Gon
<x xml:space="preserve">Abstract</x> Achieving sub‐10 nm high‐aspect‐ratio patterns from diblock copolymer self‐assembly requires both a high interaction parameter (χ, which is determined by the incompatibility between the two blocks) and a perpendicular orientation of microdomains. However, these two conditions are extremely difficult to achieve simultaneously because the blocks in a high‐χ copolymer typically have very different surface energies, favoring in‐plane microdomain orientations. A fully perpendicular orientation of a high‐χ block copolymer, poly(styrene‐block‐dimethylsiloxane) (PS‐b‐PDMS) is realized here using partially hydrolyzed polyvinyl alcohol (PVA) top coats with a solvent annealing process, despite the large surface energy differences between PS and PDMS. The PVA top coat on the block copolymer films under a solvent vapor atmosphere significantly reduces the interfacial energy difference between two blocks at the top surface and provides sufficient solvent concentration gradient in the through‐thickness direction and appropriate solvent evaporation rates within the film to promote a perpendicular microdomain orientation. The effects of interfacial energy differences and the swellability of PVA top coats controlled by the degree of hydrolysis on the orientation of microdomains are examined. The thickness of the BCP film and top coats also affects the orientation of the BCP film.